PELAKSANAAN UNDANG-UNDANG NOMOR 6 TAHUN 2014 TENTANG DESA TERKAIT PENYELENGGARAAN DESA INKLUSI DALAM PEMENUHAN HAK PENYANDANG DISABILITAS DI KABUPATEN SUKOHARJO - Larasati, Eufrasia Nadia; Madalina, Maria (Res Publica: Jurnal Hukum Kebijakan Publik, 2020)
This study aims to find out how is the implementation of Law Number 6 Year 2014 about Village related to the implementation on Inclusion Village in fulfilling Disability rights in Sukoharjo Regency. This legal research is descriptive empirical legal research with a qualitative approach. The type of data used includes primary data and secondary data. Data collection techniques are used based on data from observations and interviews with literature studies with related legal materials. The analysis technique uses qualitative data analysis techniques. Based on the results of research and discussion shows that the implementation of the Inclusion Village in Sukoharjo Regency is sufficient to provide the fulfillment of rights for people with disabilities which include participation, accessibility, and no discrimination, but not maximally yet. The implementation of the Inclusion Village has not received any monitoring or evaluation from the Village Community Empowerment Office because there is no legal authority in the form of a Regents Regulations mandating. Fulfillment of the rights of people with disabilities in Sukoharjo Regency is inseparable from barriers which include the lack of knowledge about people with disabilities, feelings of inferiority and closure both by persons with disabilities and their families, as well as activities that have not been include in the Regional Medium Term Development Plan.